Evolving Hausa Cinema from Short Dramas to Serialised Storytelling in Post-Independence Nigeria - Bello, Jamila Tahir; Ibrahim , Adamkolo Muhammed Ibrahim; Ibrahim, Abubakar Tijjani; Mukhtar , Juwairiyya Bilkisu; Dansharif, Fatima Rabiu (Feedback International Journal of Communication, 2025)
The transformation of Hausa-language cinema in Nigeria from short, stand-alone dramas to serialised storytelling represents a significant reconfiguration of regional media production. This study investigates how and why serial formats consolidated in Kannywood, focusing on the interaction between economic pressures, institutional structures, audience practices, and cultural norms in the post-independence period. Using a convergent mixed-methods design, the study combines a survey of 400 university students in Kano State, sixteen in-depth interviews with producers and directors, documentary analysis of broadcaster commissioning practices, and content analysis of selected pioneering serials. Quantitative data were analysed using descriptive statistics, while qualitative data were examined through reflexive thematic analysis, with triangulation applied to integrate findings across data sources. The findings indicate that serial production consolidated between 2012 and 2016, with accelerated growth after 2015 following the emergence of Hausa satellite broadcasters, particularly Arewa24. Audience data show strong support for serial formats, with 70.0% of respondents recognising their suitability for flexible viewing and advertising, 69.5% identifying producers as key industry drivers, and 91.0% acknowledging global media influence on narrative techniques. Interviews reveal that serialisation prompted organisational restructuring, including batch production, episodic scripting through writers’ teams, and stabilised cast and crew arrangements. At the same time, producers face persistent risks related to financing continuity, piracy, censorship, and community acceptability. The study argues that serialisation in Hausa cinema constitutes a pragmatic industrial strategy rather than a purely aesthetic shift.